Product Innovation and Digital Marketing Strategies: Key to Small Business Success in the Creative Economy Era - Habibur Rahman; Sedya Santosa; Ilham Kurniawan (Jurnal Kewirausahaan dan Bisnis, 2025)
Product innovation and digital marketing strategies are pivotal to the success of small businesses, particularly in the creative economy sector. This study explores the dynamics of small enterprises through a holistic approach encompassing product innovation, digital marketing strategies, and community support. Using a qualitative method and in-depth interviews with banana chip entrepreneurs, it identifies key factors influencing small business success.The findings reveal that innovation, such as creating new flavor variants, is critical in achieving competitive advantage. Moreover, digital marketing via social media platforms like Instagram and Facebook effectively enhances product visibility and fosters emotional connections with customers. Community support also plays a vital role by providing non-material resources such as social networks and psychological motivation, which sustain business operations.This study contributes academically by integrating theories of innovation, digital marketing, and social capital to offer a comprehensive perspective on small business dynamics. Practically, the findings recommend that small business actors adopt sustainable innovation and leverage digital technology as the main pillars of success in the creative economy era.